2020
DOI: 10.1002/kjm2.12277
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐324‐5p affects the radiotherapy response of cervical cancer via targeting ELAV‐like RNA binding protein 1

Abstract: Cervical cancer (CC) seriously threatens the health of women. Radiation therapy (RT) is the major treatment for CC. However, the recurrent CC can acquire resistance to RT. Thus, it is necessary to find a new method for reversing RT resistance in CC. It has been reported that miR‐324‐5p can suppress the progression of multiple cancers. However, whether it can reverse resistance to RT in CC remains unclear. qRT‐PCR and Western blotting were used to detect gene and protein expression in CC cells, respectively. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The overexpressing miR-15a-3p enhances radiosensitivity in cervical cancer cells by targeting tumor protein D52 to promote apoptosis ( 130 ). Additionally, the targeting of the ELAVL-1 protein via miR-324-5p increases sensitivity to ionizing radiation-induced apoptosis in cervical cancer cells ( 131 ) ( Figure 7B ).…”
Section: Noncoding Rnamentioning
confidence: 99%
“…The overexpressing miR-15a-3p enhances radiosensitivity in cervical cancer cells by targeting tumor protein D52 to promote apoptosis ( 130 ). Additionally, the targeting of the ELAVL-1 protein via miR-324-5p increases sensitivity to ionizing radiation-induced apoptosis in cervical cancer cells ( 131 ) ( Figure 7B ).…”
Section: Noncoding Rnamentioning
confidence: 99%
“…The functions of ELAVL1 have been studied in various human cancers like lung cancer 33 . Recently, it has been disclosed that ELAVL1 is associated with the progression of cervical cancers 34 . However, the relationship between circ_0060551 and ELAVL1 in cervical cancer cells has not been unveiled yet.…”
Section: Discussionmentioning
confidence: 99%
“…33 Recently, it has been disclosed that ELAVL1 is associated with the progression of cervical cancers. 34 However, the relationship between circ_0060551 and ELAVL1 in cervical cancer cells has not been unveiled yet. In our study, by conducting a series of mechanism studies, we unveiled that circ_0060551 could recruit ELAVL1 to stabilize TPD52 expression, thus influencing CC cell maliganncy.…”
Section: Circular Rnas (Circrnas) Is a New Type Of Endogenous Non-codingmentioning
confidence: 99%
“…ELAVL1 has been shown to be primarily localized at the nucleus but can translocate to the cytoplasm via phosphorylation of Y200, S202, and S221, located in the hinge region of the protein between the second and third RRM (Chen and Shyu 1995). A previous study of Ming-Jun Fan and his colleagues observed that ELAVL1 was upregulated in cervical cancer cells and was reported to promote cancer cell growth through regulating RNA in the cell cytoplasm (Fan, He et al 2020).…”
Section: )mentioning
confidence: 99%